Literatur und Film im Spiegel des Digitalen (De Gruyter, 2024)
In light of the strong media competition generated by the internet and digital television, two older and similarly endangered media formats, literature and cinema, are increasingly reflecting on their potential and limits in a process of reciprocal mirroring. This volume looks at contemporary novels and films that metafictionally discuss the other medium to discuss the forms and functions of this increasingly frequent intermedial reflexivity.